Exploring The Evolving Landscape Of Gender Roles In Society: Transformation, Challenges, And Implications - Louiza Belaid (The Journal of Studies in Language, Culture and Society)
This study explores the emerging trend of women entering traditionally male-dominated fields of work, examining the profound effects it has on gender dynamics and societal norms. The ascent of women into these professions represents a significant shift in the perceptions of gender roles, marking a crucial step towards achieving true gender equity. By shedding light on the importance of improved access to education and career opportunities, this study aims to explore the key factors driving this change and empower women to challenge the traditional gender roles. Women are increasingly pursuing a diverse range of professions, driven by changing aspirations and a desire to challenge gender stereotypes. This movement emphasizes the invaluable abilities and creativity that women bring to many fields, cultivating greater innovation and enhancing organizational performance. To gather data, we conducted an online survey with fifty-five participants from Ibn Khaldoun University, Tiaret, alongside a naturalistic observation in the same setting. It is worth noting that our sample’s selection was probabilistic. Our investigation has revealed that gender biases and barriers persist, yet women's potential for progress in male-dominated settings is still overwhelming. Overcoming these barriers necessitates institutional support, as well as workplace policies that foster an inclusive culture. This movement paves the way for a more equitable future by challenging prevailing beliefs and advocating for inclusivity, enabling individuals to thrive in their respective fields. Our collective efforts to eliminate gender barriers contribute to a more flexible workforce, benefiting both individuals and society as a whole.